THE PRACTICE OF WALIMAT AL-‘URS: Competing Sharia and Tradition in Aceh - Muhammad Nasir; Budi Juliandi (UIN Sumatera Utara, 2021)
Abstract: One of the most heated debate in a diverse and plural legal system in such as Indonesia, is the issue of harmonization of sharia and tradition. This paper is an attempt to study the extent to which the harmonization of Islamic law and tradition in Aceh. Using a qualitative approach, this paper focuses on walimat al-‘urs tradition. The author argues that differences between tradition and shari’a may become an avenue for new configuration that would be preserved as a uniting factor in the foreseeable future Indonesia. The data was obtained from in-depth interviews with important local figures. The research shows that sharia through ‘urf theoretical framework could not accepts the richness of indigenous entities.Keywords: walimat al-‘urs, ‘urf, sharia, Aceh